2014
DOI: 10.1007/s10551-014-2076-0
|View full text |Cite
|
Sign up to set email alerts
|

Giving the Gift of Goodness: An Exploration of Socially Responsible Gift-Giving

Abstract: Previous research demonstrates that consumers support firms' CSR activities, and increasingly demand socially responsible products and services. However, an implicit assumption in the extant literature is that the purchaser and the consumer of the product are the same person. The current research focuses on a unique form of socially responsible consumption behavior: giftgiving. Through thirty depth consumer interviews, we develop a typology of consumers based on whether consumers integrate CSR-related informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Consumers who were more collectivistic and more interested in group goals and sharing considered CSR practices in their personal consumption decisions. This result is relevant to the idea that CSR practices might increase awareness of CSR initiatives among consumers who are interested in SRCB (Green et al, ). The partial effect of collectivism on SRCB is supported by previous findings that consumers who engage in certain type of SRCB do not necessarily behave uniformly.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Consumers who were more collectivistic and more interested in group goals and sharing considered CSR practices in their personal consumption decisions. This result is relevant to the idea that CSR practices might increase awareness of CSR initiatives among consumers who are interested in SRCB (Green et al, ). The partial effect of collectivism on SRCB is supported by previous findings that consumers who engage in certain type of SRCB do not necessarily behave uniformly.…”
Section: Discussionmentioning
confidence: 79%
“…According to Kollmuss and Agyeman (), personal values can narrow attitude/intention‐behavior gap by increasing trial and repetition and forming habits. Especially, SRCB is strongly related to personal values (Freestone & McGoldrick, ; Green, Tinson, & Peloza, ; Lee & Kim, ; Sheth, Newman, & Gross, ). Specifically, SRCB can increase self‐enhancement, impression management, affiliation with aspirational reference groups, and communication of one's identity to significant others (Green & Peloza, ; Green et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In qualitative research studies where the samples are smaller than the quantitative ones, it is not uncommon for consumer typologies to be developed based on qualitative findings (i.e., Angell et al, 2012;Green et al, 2014;Öberseder et al, 2013). Based on this study's participants' responses on counterfeit buying behavior we divided the buyers and non-buyers into four sub-groups of consumers.…”
Section: Consumer Typologiesmentioning
confidence: 99%
“…Research on responsible consumption has explored disparate topics such as socially responsible music consumption (Green, Sinclair et al, 2016) and giftgiving (Green, Tinson, & Peloza, 2016). The former study found that consumers perceive supporting local musicians, through means such aspurchasing music or attending concerts, as a form of socially responsible consumption, while the latter suggests consumers may avoid buying products from socially responsible organizations to manage the gift-receiver's impressions of the gift-giver.…”
Section: Socially Responsible Consumptionmentioning
confidence: 99%